p130Cas mediates the transforming properties of the anaplastic lymphoma kinase. - Ambrogio, C; Voena, C; Manazza, A; Piva, R; Riera, L; Barberis, L; Costa, C; Tarone, G; Defilippi, P; Hirsch, E; Boeri Erba, E; Mohammed, S; et al. (2005)
Translocations of the anaplastic lymphoma kinase (ALK) gene have been described in anaplastic large-cell lymphomas (ALCLs) and in stromal tumors. The most frequent translocation, t(2;5), generates the fusion protein nucleophosmin (NPM)-ALK with intrinsic tyrosine kinase activity. Along with transformation, NPM-ALK induces morphologic changes in fibroblasts and lymphoid cells, suggesting a direct role of ALK in cell shaping. In this study, we used a mass-spectrometry-based proteomic approach to search for proteins involved in cytoskeleton remodeling and identified p130Cas (p130 Crk-associated substrate) as a novel interactor of NPM-ALK. In 293 cells and in fibroblasts as well as in human ALK-positive lymphoma cell lines, NPM-ALK was able to bind p130Cas and to induce its phosphorylation. Both of the effects were dependent on ALK kinase activity and on the adaptor protein growth factor receptor-bound protein 2 (Grb2), since no binding or phosphorylation was found with the kinase-dead mutant NPM-ALK(K210R) or in the presence of a Grb2 dominant-negative protein. Phosphorylation of p130Cas by NPM-ALK was partially independent from Src (tyrosine kinase pp60c-src) kinase activity, as it was still detectable in Syf-/- cells. Finally, p130Cas-/- (also known as Bcar1-/-) fibroblasts expressing NPM-ALK showed impaired actin filament depolymerization and were no longer transformed compared with wild-type cells, indicating an essential role of p130Cas activation in ALK-mediated transformation.